TRAFFICKING IN WOMEN FOR SEXUAL EXPLOITATION IN BRAZIL: THE SELECTIVE EFFECTIVENESS OF PUBLIC POLICIES THROUGH THE LENS OF GENDER AND RACE - Pereira Oliveira, Raquel; Souza Moraes, Vitor Hugo (Revista Gênero e Interdisciplinaridade, 2026)
Human trafficking constitutes a serious violation of human rights and ranks among the most profitable crimes in the world, marked by high levels of underreporting that reduce the response capacity of prevention and law-enforcement agencies. This study aims to analyze the effectiveness of Brazilian public policies to combat the trafficking of women for sexual exploitation, considering the dimensions of prevention, identification, repression, and protection, from the perspective of gender and race. It adopts a mixed-methods, exploratory-descriptive research design, grounded in a literature review and in the analysis of official data released by public authorities, covering the period from 2021 to 2024. The findings indicate that effectiveness is partial and selective: the institutional apparatus appears more active in investigation and weaker in criminal prosecution, with significant attrition between police inquiries and convictions, a lag in addressing online exploitation, and the overrepresentation of Black and brown women, who accounted for 80% of victims in 2024. The study concludes that the sophistication of criminal organizations and the structural weaknesses of the State compromise the full effectiveness of the policy and point to the need for standardizi